Preparation method of high-temperature-resistant cellulose diaphragm for lithium ion battery, diaphragm and battery
By ball milling, filtration and hot pressing the bacterial cellulose dispersion, a high-temperature resistant bacterial cellulose separator is prepared, which solves the problem of poor heat resistance of the existing separator at high temperatures, achieves higher thermal stability and ionic conductivity, and improves the charging and discharging efficiency and safety performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411992445.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing lithium-ion battery separators have poor heat resistance at high temperatures, which are prone to heat shrinkage, causing internal short circuits in contact with positive and negative electrodes, and low ionic conductivity affects the battery's charge and discharge efficiency and safety performance.
A high temperature-resistant bacterial cellulose separator was prepared by ball milling, filtering, dropping the pore-forming agent and then hot-pressing. This method improves the thermal stability and pore structure of the membrane and enhances the migration channels of lithium ions.
It improves the dimensional stability and structural integrity of the diaphragm at high temperatures, reduces the heat shrinkage rate, enhances the ionic conductivity, and improves the charging and discharging efficiency and thermal safety performance of the battery.
Smart Images

Figure CN119674439A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a method for preparing a high-temperature resistant cellulose diaphragm for lithium-ion batteries, a diaphragm and a battery. Background Art
[0002] Lithium-ion batteries are secondary batteries that rely mainly on the intercalation and deintercalation of lithium ions between the positive and negative electrodes to achieve the charging and discharging process. During charging, an external power source drives lithium ions to be deintercalated from the positive electrode material, migrate through the electrolyte to the negative electrode material and embed therein; during discharging, the opposite is true, lithium ions are deintercalated from the negative electrode material, return to the positive electrode material through the electrolyte, and electrons flow from the negative electrode to the positive electrode through an external circuit, thereby generating current for external devices to use. Compared with traditional batteries such as lead-acid batteries and nickel-cadmium batteries, lithium-ion batteries have higher energy density and longer cycle life, and are widely used in electric vehicles, mobile electronic devices and other fields.
[0003] The main materials of lithium-ion batteries are positive electrode, negative electrode, electrolyte, diaphragm and shell, among which the diaphragm is one of the important main materials. The diaphragm of conventional lithium-ion batteries is based on polypropylene (PP) and polyethylene (PE) materials, and the surface is coated with polyvinylidene fluoride (PVDF) and ceramic materials. However, such high molecular polymer diaphragms with PP and PE as the base film have poor heat resistance. At high temperatures, the diaphragm is prone to thermal shrinkage, resulting in internal short circuits between the positive and negative electrodes, causing safety problems such as fire and explosion; and the chemical polarity of the diaphragm is relatively small, and its affinity with the highly polar electrolyte is relatively poor, so the electrolyte and the diaphragm have a large contact angle, resulting in greater obstacles for the free lithium ions in the electrolyte to pass through the diaphragm, making the resistance of the diaphragm part of the battery's internal resistance larger, which is not conducive to the discharge of the battery; the mechanical strength is not high, and lithium batteries are prone to generate lithium dendrites on the surface of the negative electrode when working under unconventional conditions (low temperature). The generated lithium dendrites are easy to pierce the diaphragm, causing short circuit failure and fire in the battery.
[0004] Therefore, it is necessary to develop a lithium-ion battery separator that has both strong heat resistance and ionic conductivity. Summary of the invention
[0005] In order to solve or partially solve the problems existing in the related art, the present application provides a method for preparing a high-temperature resistant cellulose membrane for a lithium-ion battery, a membrane and a battery, which can improve the high-temperature resistance of the membrane, and can still maintain good dimensional stability and structural integrity at higher temperatures. At the same time, it has a rich and suitable pore structure, which can provide a large number of channels for the migration of lithium ions, so that the battery maintains a high charge and discharge efficiency and good safety performance.
[0006] The first aspect of the present application provides a method for preparing a high temperature resistant cellulose separator for a lithium ion battery, comprising the following steps: S1, performing ball milling pretreatment on the bacterial cellulose dispersion to obtain a pretreated dispersion; S2, filtering the pretreated dispersion and simultaneously adding a pore-forming agent thereto to obtain a bacterial cellulose membrane; S3, subjecting the bacterial cellulose membrane to a heat pressing treatment to obtain a bacterial cellulose membrane.
[0007] In some embodiments of the present application, in step S1, the ball milling pretreatment speed is 150-350 r / min, and the pretreatment time is 25-60 min.
[0008] In some embodiments of the present application, the solid content of the bacterial cellulose dispersion is 0.5-1.0 wt %; the diameter of the bacterial cellulose in the bacterial cellulose dispersion is 50-100 nm, and the length is ≥20 μm.
[0009] In some embodiments of the present application, the volume ratio of bacterial cellulose with a diameter of 50-75 nm to bacterial cellulose with a diameter of 75-100 nm in the bacterial cellulose dispersion is (2-4):1.
[0010] In some embodiments of the present application, in the filtration process in step S2, positive pressure or negative pressure is applied to the pretreated dispersion for filtration.
[0011] In some embodiments of the present application, in step S2, the pre-treated dispersion is vacuum filtered with a vacuum degree of 0.08-0.1 MPa; and the filtering treatment time is 3-10 min.
[0012] In some embodiments of the present application, the pore-forming agent is selected from at least one of ethanol, isopropanol, acetone, and n-butanol.
[0013] In some embodiments of the present application, the total volume usage of the pore-forming agent is 1.2 to 2 times the volume of the bacterial cellulose dispersion.
[0014] In some embodiments of the present application, the dripping rate of the pore-forming agent is 0.1-0.2 mL / s, and the dripping is continued for 1-4 min.
[0015] In some embodiments of the present application, in step S3, the temperature of the hot pressing treatment is 45-60° C., the pressure is 0.1-0.2 MPa, and the treatment time is 30-60 min.
[0016] A second aspect of the present application provides a high temperature resistant cellulose separator for lithium ion batteries, which is prepared by the above preparation method.
[0017] A third aspect of the present application provides a lithium-ion battery, comprising the above-mentioned high temperature resistant cellulose separator.
[0018] The technical solution provided by this application may have the following beneficial effects: The bacterial cellulose membrane obtained by ball milling pretreatment of bacterial cellulose dispersion and adding pore-forming agent during filtration and then hot pressing has high thermal stability, can maintain good dimensional stability and structural integrity at high temperatures, has low thermal shrinkage, and can effectively prevent excessive shrinkage or melting of the membrane when abnormal conditions such as thermal runaway occur in the battery, avoid short circuit between the positive and negative electrodes, and improve the thermal safety performance of the battery. Moreover, it has a rich and suitable pore structure, which can provide a large number of channels for the migration of lithium ions, allowing lithium ions to quickly move between the positive and negative electrodes through the membrane, thereby improving the charge and discharge efficiency of the battery, and the hydroxyl and other functional groups rich in the surface of the bacterial cellulose membrane can enhance the affinity and adsorption capacity of the electrolyte, so that the electrolyte can better infiltrate the membrane, further ensuring the smoothness of ion conduction, helping to reduce the internal resistance of the battery and improve the overall performance of the battery.
[0019] Moreover, the bacterial cellulose in the bacterial cellulose dispersion has a high specific surface area and length. After forming a film, it has high mechanical strength and can maintain high stability and strength, meeting the mechanical requirements of lithium-ion batteries for diaphragms during use; and it has good tensile properties and flexibility, and can use the volume changes of electrode materials during the charging and discharging process of lithium-ion batteries, reduce the mechanical stress on the diaphragm caused by electrode expansion and contraction, and improve the battery's cycle stability and safety performance.
[0020] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail the exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.
[0022] Figure 1 is a scanning electron microscope image of the high temperature resistant cellulose separator for lithium ion batteries obtained in Example 1 of the present application; Figure 2 This is a scanning electron microscope image of the cellulose membrane obtained in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0023] To make the present invention easy to understand, the present invention will be described in detail below. However, before describing the present invention in detail, it should be understood that the present invention is not limited to the specific embodiments described. It should also be understood that the terms used herein are only for describing specific embodiments and are not intended to be limiting.
[0024] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0025] Where a numerical range is provided, it is to be understood that each intermediate value between the upper and lower limits of the range and any other provisions or intermediate values in the specified range is encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included in the smaller ranges and are also encompassed within the present invention, subject to any explicitly excluded limits in the specified range. Where a specified range includes one or two limits, the scope excluding any or both of those included limits is also encompassed within the present invention. In the description of the present application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically limited.
[0026] Unless otherwise defined, all terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials or equivalent methods and materials described herein can also be used in the practice or testing of the present invention, preferred methods and materials are now described.
[0027] Such high molecular polymer diaphragms with PP and PE as base films have poor heat resistance. When the temperature is high, the diaphragm is prone to thermal shrinkage, resulting in internal short circuit when the positive and negative electrodes contact each other, causing safety problems such as fire and explosion. In addition, the chemical polarity of the diaphragm is relatively small, and its affinity with the highly polar electrolyte is relatively poor. Therefore, there is a large contact angle between the electrolyte and the diaphragm, resulting in greater resistance for the lithium ions free in the electrolyte to pass through the diaphragm, making the resistance of the diaphragm part of the battery's internal resistance relatively large, which is not conducive to the discharge of the battery. The mechanical strength is not high. When the lithium battery works under unconventional conditions (low temperature), it is easy to generate lithium dendrites on the surface of the negative electrode. The generated lithium dendrites can easily pierce the diaphragm, causing the battery to have problems such as short circuit failure and fire.
[0028] In response to the above problems, the embodiments of the present application provide a method for preparing a high-temperature resistant cellulose membrane for a lithium-ion battery, a membrane and a battery, which can improve the high-temperature resistance of the membrane, and can still maintain good dimensional stability and structural integrity at higher temperatures. At the same time, it has a rich and suitable pore structure, which can provide a large number of channels for the migration of lithium ions, thereby allowing the battery to maintain a high charge and discharge efficiency and good thermal safety performance.
[0029] The high temperature resistant cellulose membrane for lithium ion batteries of the embodiment of the present application is prepared by the following preparation method. The preparation method of the high temperature resistant cellulose membrane for lithium ion batteries comprises the following steps: S1, performing ball milling pretreatment on the bacterial cellulose dispersion to obtain a pretreated dispersion; S2, filtering the pretreated dispersion and simultaneously adding a pore-forming agent thereto to obtain a bacterial cellulose membrane; S3. The bacterial cellulose membrane is subjected to heat pressing to obtain a bacterial cellulose membrane.
[0030] In the above steps, firstly, the bacterial cellulose dispersion is pretreated by ball milling in step S1, so that the jelly-like bacterial cellulose dispersion can be ball milled to remove the non-freely flowing water molecules attached to the fiber surface, and obtain a bacterial cellulose dispersion with good fluidity. Ball milling pretreatment causes the fibers of the bacterial cellulose to be impacted, sheared and rubbed by the grinding medium, resulting in rearrangement between the fibers, making the interweaving more complex, and being conducive to forming a more dense, uniform, and higher porosity network structure. Moreover, the mechanical force generated by ball milling will destroy the hydrogen bonds between the bacterial cellulose molecular chains, reduce the crystallinity of cellulose, increase the amorphous region, and be conducive to improving the flexibility and elasticity of the bacterial cellulose film, and make the hydrophilicity of the bacterial cellulose film better, thereby improving its wetting properties.
[0031] In the above step S2, a pore-forming agent is added dropwise during the filtration and film-forming process of the pre-treated dispersion to obtain a bacterial cellulose membrane. The addition of the pore-forming agent will form additional pores in the bacterial cellulose membrane, increase the porosity of the membrane, and prevent the fibers from being stacked too tightly, making the arrangement of the fibers looser, improving the flexibility of the bacterial cellulose membrane after film formation, and making the diaphragm less prone to brittle fracture during the use of the battery. The pores formed by the pore-forming agent increase the specific surface area of the bacterial cellulose membrane, increase its surface energy and active sites, and form a highly stable SEI membrane between the diaphragm and the pole piece during the battery formation process, thereby improving the battery's cycle performance.
[0032] In the above step S3, the bacterial cellulose membrane obtained by hot pressing is dehydrated and the fibers are more tightly bonded, thereby improving the strength of the membrane and preventing the membrane from being broken or damaged by external forces during battery assembly and battery charge and discharge cycles, thereby maintaining the integrity of the membrane and reducing the risk of battery short circuit and improving battery safety and cycle stability.
[0033] At the same time, through the combination of the above steps, the thermal stability of the bacterial cellulose membrane is improved, and the membrane is not prone to shrinkage, deformation or melting in a high temperature environment. It can effectively avoid the short circuit problem caused by direct contact between the positive and negative electrodes of the battery, improve the safety and reliability of the battery under high temperature conditions, and reduce the safety hazards caused by thermal runaway.
[0034] In some embodiments, the ball milling pretreatment speed in step S1 is 150-350 r / min, and the pretreatment time is 25-60 min. If the ball milling pretreatment speed is too high or the pretreatment time is too long, the mechanical force generated by the ball milling will cause the fiber length to be greatly broken into shorter fiber fragments, and the crystallinity will be seriously reduced, which will also cause the thermal stability of the membrane to decrease, reducing the overall strength and thermal stability of the bacterial cellulose membrane. If the ball milling pretreatment speed is too low or the pretreatment time is too short, it will not be able to remove the non-free flowing water molecules attached to the fiber surface, and a bacterial cellulose dispersion with good fluidity will not be obtained, which is not conducive to the subsequent formation of a uniform and stable bacterial cellulose membrane.
[0035] In some embodiments, the solid content of the bacterial cellulose dispersion is 0.5-1.0wt%. Specifically, for example, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, etc., or any value within the above range. If the solid content in the bacterial cellulose dispersion is too low, the amount of cellulose is small and it is difficult to form a continuous, complete, and high-strength membrane structure, and the thickness of the formed bacterial cellulose membrane is too thin and the porosity is too high, which is difficult to meet the requirements of ensuring its mechanical strength and barrier properties in lithium ion battery materials. If the solid content in the bacterial cellulose dispersion is too high, the cellulose is easy to agglomerate with each other, the fluidity is low, and the dispersion is uneven, which will result in uneven thickness and low porosity of the obtained bacterial cellulose membrane, and the drying time is greatly extended, which will reduce production efficiency in industrial production.
[0036] In some embodiments, the diameter of bacterial cellulose in the bacterial cellulose dispersion is 50-100 nm, and the length is ≥20 μm. By controlling the diameter and length of bacterial cellulose, the bacterial cellulose can be easily intertwined and entangled in the dispersion to form a uniform film, and the porosity of the film can be increased after film formation, ensuring that it has good thermal stability, porosity and tensile strength.
[0037] In some embodiments, the volume ratio of bacterial cellulose with a diameter of 50-75 nm to bacterial cellulose with a diameter of 75-100 nm in the bacterial cellulose dispersion is (2-4):1. By controlling the diameter of the bacterial cellulose in the bacterial cellulose dispersion to be distributed in a gradient manner and strictly regulating the volume ratio of the two, the porosity of the bacterial cellulose membrane can be improved while ensuring good density, tensile strength, and thermal stability. If there are too many bacterial celluloses with smaller diameters in the bacterial cellulose dispersion, a more compact stacking network structure can be formed, but the porosity of the membrane will be reduced; if there are too many bacterial celluloses with larger diameters, the porosity of the bacterial cellulose membrane can be guaranteed, but the loose structure of the membrane may affect the strength and heat resistance of the membrane.
[0038] In some embodiments, during the filtration process in step S2, positive pressure or negative pressure is applied to the pre-treated dispersion for filtration. When negative pressure is applied, a high vacuum can be formed, so that volatile substances such as water in the bacterial cellulose dispersion are more easily volatilized and removed, which plays a role in improving the film-forming efficiency, while enhancing the hydrogen bonding effect between cellulose molecules, thereby improving the crystallinity and tensile strength of the film; when positive pressure is applied, volatile substances such as water in the bacterial cellulose dispersion are more easily volatilized and removed by pressure, which plays a role in improving the film-forming efficiency.
[0039] In some embodiments, the pre-treated dispersion is vacuum filtered in step S2, and the vacuum degree is 0.08-0.1 MPa; the filtering time is 3-10 min. The vacuum degree and filtering time of the vacuum filtration film can be adjusted according to the specific parameters of the film thickness requirements and the solid content in the dispersion.
[0040] In some embodiments, the pore-forming agent is selected from at least one of ethanol, isopropanol, acetone, and n-butanol, preferably ethanol. The pore-forming agent is a hydrophilic and lipophilic solvent, and the water molecules in the bacterial cellulose membrane can be displaced through the mutual collision between the pore-forming agent and the bacterial cellulose membrane, thereby increasing the porosity of the bacterial cellulose membrane.
[0041] In some embodiments, the total volume of the pore-forming agent is 1.2 to 2 times the volume of the bacterial cellulose dispersion. By controlling the total amount of the pore-forming agent, and by dripping, the pore-forming agent can be distributed more evenly in the cellulose network, the fibers can be effectively separated, and pores of relatively uniform size and appropriate porosity can be formed, which is conducive to improving the performance stability of the membrane, and can improve the porosity while ensuring that the membrane structure has sufficient density to ensure that the diaphragm maintains sufficient strength and thermal stability when used in lithium-ion batteries. When the amount of the pore-forming agent is too high, the porosity on the bacterial cellulose membrane will increase, and larger pores will be formed, which will affect the mechanical properties of the bacterial cellulose membrane and cannot ensure its strength and barrier properties; when the amount of the pore-forming agent is too low, the number of pores formed is relatively small and the pore size is small, and the pore size distribution may be uneven due to the relatively sparse distribution of the pore-forming agent.
[0042] In some embodiments, the pore-forming agent is dripped at a rate of 0.1 to 0.2 mL / s for 1 to 4 min. The dripping rate and dripping time of the pore-forming agent can be adjusted according to the total amount of the pore-forming agent and the volume of the bacterial cellulose dispersion.
[0043] In some embodiments, in step S3, the temperature of the hot pressing treatment is 45-60° C., the pressure is 0.1-0.2 MPa, and the treatment time is 30-60 min. The drying treatment temperature and treatment time can be adjusted according to the required thickness of the diaphragm.
[0044] The battery provided in the embodiment of the present application includes the above-mentioned diaphragm, which can solve the safety problem caused by thermal shrinkage of PP or PE film at high temperature, increase the upper limit temperature of thermal shrinkage of the diaphragm, so that the diaphragm can maintain its appearance without obvious deformation at high temperature; reduce the impedance of the diaphragm, improve the ionic conductivity, and increase the rate performance; enhance the mechanical strength of the diaphragm, and improve the safety performance of the lithium-ion battery.
[0045] The diaphragm provided in the embodiment of the present application is suitable for lithium-ion batteries.
[0046] The lithium-ion battery further comprises a negative electrode sheet, a positive electrode sheet and an electrolyte, wherein the negative electrode sheet may be a negative electrode sheet comprising silicon material.
[0047] The lithium-ion battery involved in the embodiment of the present application includes a diaphragm prepared by the above method.
[0048] Lithium-ion batteries also include electrolyte, negative electrode sheets and positive electrode sheets. The negative electrode sheets, separators and positive electrode sheets are stacked in sequence and can be made into battery cells through a winding process or a lamination process. The battery cells are loaded into the aluminum-plastic film that has been punched and formed, and the battery cells are baked. Then, the electrolyte is injected into the baked and dried battery cells so that the battery cells are immersed in the electrolyte. Then, vacuum packaging, standing, formation and other processes are performed to complete the preparation of lithium-ion batteries.
[0049] The electrolyte, the negative electrode plate and the positive electrode plate can be made of any known materials, and this application does not limit this.
[0050] In some embodiments, the positive electrode sheet described in the present application may include a positive electrode current collector and a positive electrode material layer coated on the surface of the positive electrode current collector. The positive electrode current collector is a conventional metal foil or a composite current collector, such as aluminum foil.
[0051] In some embodiments, the positive electrode material layer is formed by coating the positive electrode slurry on the surface of the positive electrode current collector.
[0052] In some embodiments, the positive electrode slurry includes a positive electrode active material, a conductive agent and a binder. The positive electrode active material includes, but is not limited to, one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, and ternary LiNixCoyMnzO2 materials (where x+y+z=1, x≥y). The conductive agent includes, but is not limited to, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The binder includes, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0053] In some embodiments, the negative electrode sheet described in the present application may include a negative electrode current collector and a negative electrode material layer located on the surface of the negative electrode current collector. The negative electrode current collector mentioned in the present application is not particularly limited, as long as it can achieve the purpose of the present application, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.
[0054] The negative electrode material layer includes a negative electrode active material, a conductive agent and a binder. Specifically, the negative electrode material layer is formed by mixing the negative electrode active material, the conductive agent and the binder into a negative electrode slurry, and then coating the negative electrode slurry on the surface of the negative electrode current collector.
[0055] In some embodiments, the negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy.
[0056] The carbon material conductive agent may include at least one of carbon nanotubes, carbon nanofibers, graphene, artificial graphite, natural graphite and mesophase carbon microspheres.
[0057] The binder may include one or more of lithium carboxymethyl cellulose (CMC-Li), sodium carboxymethyl cellulose (CMC-Na), potassium carboxymethyl cellulose (CMC-K), styrene-butadiene rubber (SBR), styrene acrylic emulsion, lithium polyacrylate (PAA-Li), sodium polyacrylate (PAA-Na), potassium polyacrylate (PAA-K), lithium alginate (ALG-Li), sodium alginate (ALG-Na) and potassium alginate (ALG-K).
[0058] In some embodiments, the electrolyte described in the present application may be selected from an electrolyte comprising a solvent, an additive and a lithium salt. Among them, the lithium salt may be selected from at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium bisfluorooxalate borate, lithium bisoxalate borate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylimide, lithium difluorooxalate phosphate, and lithium perchlorate. The concentration of the lithium salt in the electrolyte is 0.9mol / L to 1.3mol / L. The solvent may be selected from one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate, and the carboxylic acid ester solvent may be selected from one or more of ethyl propionate, ethyl acetate, and propyl propionate. The additive may be selected from one or more of ethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, methylene carbonate, fluorocarbonate, trifluoromethyl carbonate, and bisfluorocarbonate. The components may be freely combined without particular restrictions.
[0059] The present application also provides an electrical device or various energy storage systems using batteries as energy storage elements. Electrical devices include but are not limited to mobile phones, tablets, computers, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc.
[0060] In order to make the present invention easier to understand, the present invention will be further described in detail below in conjunction with examples, which are merely illustrative and are not intended to limit the scope of application of the present invention. The raw materials or components used in the present invention can be obtained by commercial routes or conventional methods unless otherwise specified.
[0061] Example 1 Preparation of lithium-ion battery (1) Preparation of high temperature resistant cellulose membrane 1. Put 20mL of bacterial cellulose dispersion with a solid content of 0.8wt% (the volume ratio of bacterial cellulose with a diameter of 50-75nm to bacterial cellulose with a diameter of 75-100nm in the bacterial cellulose dispersion is 2:1, and the length is ≥20μm) into a ball mill and mill at a speed of 300r / min for 30min to obtain a pretreated dispersion; 2. Use a syringe to slowly drip the ball-milled pre-treated dispersion into the filtration funnel, spread the dispersion flat on the filter paper, turn on the filtration machine for filtration treatment, and observe whether the water in the pre-treated dispersion is fully drained after about 3 minutes of treatment. After drying, the pre-treated bacterial cellulose membrane is obtained; 3. Add ethanol to the pretreated bacterial cellulose membrane under filtration at a dripping rate of 0.2 mL / s. The total volume of ethanol added is 36 mL. After the ethanol is drained, the bacterial cellulose membrane is obtained. 4. Place a flat glass plate on a constant temperature heating table, and place a new filter paper on the glass plate. Use tweezers to peel the bacterial cellulose membrane off the filter paper and place it on the filter paper. Then cover it with another piece of filter paper and then the flat glass plate. Add a 2 kg weight on top, heat the hot table to 60 ° C and heat press for 30 minutes to obtain the bacterial cellulose membrane.
[0062] (2) Preparation of electrolyte Ethylene carbonate EC, diethyl carbonate DEC, and propylene carbonate PC were mixed in a mass ratio of 1:1:1 to obtain a solvent. Then, based on the total mass of the electrolyte, 1% of an additive (fluoroethylene carbonate) was added and mixed, and then lithium salt LiPF6 was added and mixed evenly to obtain an electrolyte.
[0063] (3) Preparation of positive electrode sheet Lithium cobalt oxide (LiCoO2), conductive carbon black and polyvinylidene fluoride (PVDF) are added into N-methylpyrrolidone (NMP) solvent in a mass ratio of 97:1.5:1.5 and stirred thoroughly to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, and a positive electrode sheet that meets the winding requirements is made through processes such as drying, cold pressing and sheet making.
[0064] (4) Preparation of negative electrode sheet Graphite, silicon material, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber are added to a deionized water solvent in a mass ratio of 93:6:5:1:1 and stirred thoroughly to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on each surface of the negative electrode current collector copper foil, and a negative electrode sheet that meets the winding requirements is obtained through drying, cold pressing, sheet making and other processes.
[0065] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrodes to play a role of isolation, and then the stacked electrode sheet and separator are wound to obtain a bare cell. The bare cell is placed in the aluminum-plastic film that has been punched and formed, and the top and side are sealed. After drying, the electrolyte is injected, and after packaging, the clamp is clamped and divided into components to obtain a lithium-ion battery.
[0066] Example 2 The difference from Example 1 is that the volume ratio of bacterial cellulose with a diameter of 50-75 nm to bacterial cellulose with a diameter of 75-100 nm in the bacterial cellulose dispersion is 1:1, and the length is ≥20 μm.
[0067] Example 3 The difference from Example 1 is that the volume ratio of bacterial cellulose with a diameter of 50-75 nm to bacterial cellulose with a diameter of 75-100 nm in the bacterial cellulose dispersion is 4:1, and the length is ≥20 μm.
[0068] Example 4 The difference from Example 1 is that the volume ratio of the amount of ethanol added to the bacterial cellulose dispersion is 1:1.
[0069] Example 5 The difference from Example 1 is that the volume ratio of the amount of ethanol added to the bacterial cellulose dispersion is 3:1.
[0070] Comparative Example 1 The difference from Example 1 is that ethanol is not used for pore-forming treatment during the preparation of the diaphragm.
[0071] Comparative Example 2 The difference from Example 1 is that the membrane preparation steps include: 1. Use a syringe to slowly drip 20mL of bacterial cellulose dispersion with a solid content of 0.8wt% into the suction funnel, spread the dispersion on the filter paper, turn on the suction filter for suction treatment, and observe whether the water in the pre-treated dispersion is fully drained after about 3 minutes of treatment. After drying, the pre-treated bacterial cellulose membrane is obtained; 2. Add ethanol to the pretreated bacterial cellulose membrane under filtration at a drip rate of 0.2 mL / s for about 3 minutes. After the ethanol is drained, the bacterial cellulose membrane is obtained. 3. Place a flat glass plate on a constant temperature heating table, and place a new filter paper on the glass plate. Use tweezers to peel the bacterial cellulose membrane off the filter paper and place it on the filter paper. Then cover it with another piece of filter paper and then the flat glass plate. Add a 2 kg weight on top, heat the hot table to 60 ° C and heat press for 30 minutes to obtain the bacterial cellulose membrane.
[0072] Comparative Example 3 The difference from Example 1 is that the membrane preparation steps include: 1. Place 20 mL of bacterial cellulose dispersion with a solid content of 0.8 wt% into a ball mill and mill at a speed of 300 r / min for 30 min to obtain a pretreated dispersion; 2. Use a syringe to slowly drip the ball-milled pre-treated dispersion into the filtration funnel, spread the dispersion on the filter paper, turn on the filtration machine for filtration treatment, and obtain the pre-treated bacterial cellulose membrane after about 3 minutes of treatment; 3. Pour ethanol onto the pretreated bacterial cellulose membrane after filtration to make the ethanol completely infiltrate the pretreated bacterial cellulose membrane. After infiltration for about 20 minutes, the bacterial cellulose membrane is obtained; 4. Place a flat glass plate on a constant temperature heating table, and place a new filter paper on the glass plate. Use tweezers to peel the bacterial cellulose membrane off the filter paper and place it on the filter paper. Then cover it with another piece of filter paper and then the flat glass plate. Add a 2 kg weight on top, heat the hot table to 60 ° C and heat press for 30 minutes to obtain the bacterial cellulose membrane.
[0073] Comparative Example 4 The difference from Example 1 is that the separator is a PP separator of the same thickness.
[0074] The composite diaphragms and lithium-ion batteries prepared in the above-mentioned embodiments and comparative examples were subjected to the following performance tests.
[0075] 1. Diaphragm physical property test 1) Thermal shrinkage test Cut the diaphragm into samples of 100mm*100mm along MD and TD directions; clamp the sample with A4 paper, put it into a 120℃ oven and bake it for 1h, then take it out and cool it; measure the size L of the diaphragm after cooling with a steel ruler; calculate the thermal shrinkage rate (%) = (100-L) / 100.
[0076] 2) Tensile strength test Cut the diaphragm into 100mm*100mm samples along the MD and TD directions. Clamp the samples with A4 paper, bake them in a 120℃ oven for 1h, then take them out and cool them down. Use a high-speed tensile tester with a tensile speed of 100mm / min to test the tensile strength of the diaphragm after high-temperature treatment.
[0077] 3) Ionic conductivity test The ionic conductivity of the separator was studied by recording the electrochemical impedance spectroscopy (EIS) of the separator. The impedance measurement was performed by maintaining the frequency range of 50 Hz to 500 Hz and the amplitude of 5 mV. The ionic conductivity σ was calculated as follows: σ=d / (Rb·S); Where d is the thickness of the diaphragm, in cm; Rb is the bulk resistance, in Ω; S is the area of the symmetrical electrode, in cm 2 .
[0078] The test results are recorded in Table 1.
[0079] 4) Pore size distribution test The membranes of Example 1 and Comparative Example 1 were observed using a scanning electron microscope (SEM). Figure 1 and Figure 2 shown.
[0080] 2. Lithium-ion battery performance test 1) Cycle performance test The battery was placed in a 25℃ environment for more than 2 hours, charged to full power at 0.5C, cut off at 0.02C, and tested for discharge capacity; discharged to 3.0V at 0.5C, and left for 10 minutes; charged to full power at 0.5C, cut off at 0.02C, and left for 10 minutes; repeated 2-3 steps until the cycle was 400 times, and the battery discharge capacity was measured after the cycle was completed. The capacity retention rates calculated for each group of 5 batteries after the cycle were averaged and recorded in Table 1.
[0081] Capacity retention rate (%) = (discharge capacity after 400 cycles) / (initial discharge capacity) * 100% 2) Thermal shock test The battery obtained from the above-mentioned embodiment and comparative example separator was heated by convection or circulating hot air oven at a starting temperature of (25±3)°C, a heating rate of (5±2)°C / min, and the temperature was raised to (140±2)°C. The test was terminated after maintaining for 60 minutes to observe whether the battery cell had thermal runaway. The test results are recorded in Table 1.
[0082] Table 1 Test results
[0083] Attached Figure 1 The scanning electron microscope image of the diaphragm prepared by the method of Example 1 is attached. Figure 2 This is a scanning electron microscope image of the diaphragm prepared by the method of Comparative Example 1. Figure 1 The diaphragm prepared by the method described in the embodiment of the present application has high porosity and a complex fiber interweaving network. Figure 2 The porosity of the diaphragm prepared by the method described in Comparative Example 1 is low.
[0084] The comparison of the data of Example 1 and Comparative Example 1 shows that the bacterial cellulose membrane has low porosity and low ion conductivity without pore-forming treatment with a pore-forming agent, which is not conducive to the embedding and extraction of lithium ions between the positive and negative electrodes, and the internal resistance of the battery is large, which will deteriorate the cycle performance of the battery. However, the diaphragm treated with a pore-forming agent has high porosity and high ion conductivity, which can provide a large number of channels for the migration of lithium ions, allowing lithium ions to quickly move between the positive and negative electrodes through the diaphragm, thereby improving the charge and discharge efficiency of the battery, and at the same time, it can effectively prevent the diaphragm from rupture or deformation due to external forces, thereby avoiding safety problems such as short circuits caused by direct contact between the positive and negative electrodes, and improving the reliability and safety of the battery.
[0085] Comparison of the data of Example 1 and Comparative Example 2 shows that a bacterial cellulose film with higher uniformity can be obtained by subjecting the bacterial cellulose to ball milling pretreatment and then film forming treatment, thereby improving its mechanical strength, heat resistance and ionic conductivity, and enhancing the dynamic performance and service life of the battery when the separator is used in a lithium-ion battery.
[0086] Comparison of the data of Example 1 and Comparative Example 3 shows that the pore-forming agent is added dropwise and a negative pressure is applied to form a vacuum during the film-forming process, which not only helps to remove volatile substances such as water and improve the film-forming efficiency, but also can avoid the pore-forming agent from causing significant damage to the fiber structure of bacterial cellulose while quickly forming pores, thereby ensuring that the diaphragm has good mechanical properties, chemical stability and thermal stability, and improving the service life, dynamic performance and safety performance of the battery.
[0087] The data comparison between Example 1 and Comparative Example 4 shows that the bacterial cellulose membrane prepared by the method of the present application has good heat resistance, mechanical properties and ionic conductivity compared with the traditional PP membrane, and can significantly improve the cycle stability, safety performance and kinetic performance of the battery.
[0088] Comparison of the data from Examples 1-3 shows that controlling the diameter and length of the bacterial cellulose in the bacterial cellulose dispersion within an appropriate range can further improve the porosity, heat resistance and mechanical strength of the diaphragm.
[0089] Comparison of the data from Example 1, Example 4, and Example 4 shows that controlling the amount of pore-forming agent added and the amount of bacterial cellulose dispersion in the bacterial cellulose membrane formation process within an appropriate range can further improve the porosity, heat resistance, and mechanical strength of the membrane.
[0090] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present application may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.
Claims
1. A method for preparing a high temperature resistant cellulose separator for lithium ion batteries, characterized in that: The following steps are involved: S1, performing ball milling pretreatment on the bacterial cellulose dispersion to obtain a pretreated dispersion; S2, filtering the pretreated dispersion and simultaneously adding a pore-forming agent thereto to obtain a bacterial cellulose membrane; S3, subjecting the bacterial cellulose membrane to a heat pressing treatment to obtain a bacterial cellulose membrane.
2. The preparation method according to claim 1, characterized in that: In step S1, the ball milling pretreatment speed is 150-350 r / min, and the pretreatment time is 25-60 min.
3. The preparation method according to claim 1, characterized in that: The solid content of the bacterial cellulose dispersion is 0.5-1.0 wt %; the diameter of the bacterial cellulose in the bacterial cellulose dispersion is 50-100 nm, and the length is ≥20 μm.
4. The preparation method according to claim 1, characterized in that: The volume ratio of bacterial cellulose with a diameter of 50-75 nm to bacterial cellulose with a diameter of 75-100 nm in the bacterial cellulose dispersion is (2-4):
1.
5. The preparation method according to claim 1, characterized in that: In the filtration process in step S2, positive pressure or negative pressure is applied to the pretreated dispersion for filtration.
6. The preparation method according to claim 1, characterized in that: In the step S2, the pre-treated dispersion is vacuum filtered with a vacuum degree of 0.08-0.1 MPa; and the filtering treatment time is 3-10 min.
7. The preparation method according to claim 1, characterized in that: The pore-forming agent is selected from at least one of ethanol, isopropanol, acetone, and n-butanol; And / or, the total volume usage of the pore-forming agent is 1.2 to 2 times the volume of the bacterial cellulose dispersion; And / or, the dripping rate of the pore-forming agent is 0.1-0.2 mL / s.
8. The preparation method according to claim 1, characterized in that: In step S3, the temperature of the hot pressing treatment is 45-60° C., the pressure is 0.1-0.2 MPa, and the treatment time is 30-60 min.
9. A high temperature resistant cellulose separator for lithium ion batteries, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: Including the high temperature resistant cellulose diaphragm as described in claim 9.
Citation Information
Patent Citations
Bacterial cellulose-based micropore composite film and preparation method and application thereof
CN106299213A
Thin-film sheet including cellulose fine-fiber layer
CN107075804A
Method used for controllable synthesis of hierarchical pore metal oxide catalyst with bacterial cellulose
CN110052274A
Cellulose-based lithium battery flame-retardant diaphragm and preparation method thereof
CN112201905A
Composite modified cellulose nylon diaphragm as well as preparation method and application thereof
CN117096547A